Analysis and control of aquatic locomotion on robotic fish - Eric Purnama (2014)
Biomimetic approach is very profound in the search of a more effective and efficient ways of performing tasks. This includes the development of autonomous underwater vehicles (AUVs). Robotic fishes have various applications ranging from marine explorations to defense related uses. In this project, the author developed biomimetic shark, whose swimming mechanism is categorized under thunniform, one of the most efficient swimmers. All four main shark fins were applied in the robot, namely Caudal fin, Pectoral fins, and Dorsal fin.